The untouchables [videorecording (DVD)] - De Palma, Brian; Costner, Kevin; Connery, Sean; Smith, Charles Martin; Garcia, Andy; Ness, Eliot (Paramount, 2004)
A larger-than-life depiction of Al Capone, the warlord who ruled Prohibition-era Chicago ... and Eliot Ness, the law enforcer who vowed to bring him down. In this classic confrontation between good and evil, Ness learns, with the help of a cop named Malone, how to beat the mob by shooting fast and shooting first.